Rereading and Discussing Drama Text “Topekkong Agreement” in Stimulate Students’ English Performance - Syukri, Muhammad; Amir, Rahma Melati; Amin, Fatimah Hidayahni (JLE: Journal of Literate of English Education Study Program, 2025)
The objective of the research is to find out and describe how can rereading and discussing drama text “Topekkong Agreement “stimulate the students English performance. The research applied Mixed Method, combines quantitative and qualitative approach by essentially mixing both quantitative and qualitative data in a single study. The purpose of mixed methods research is to build up the synergy and strength exist between quantitative and qualitative research methods in order to fully understand a phenomenon is possibly using either qualitative or quantitative alone. The object of the research was the fifth grade of English and Literature Department that cconsisted of 28 students whom were divided into sixt group discussions. The research result indicates that students’ English Performance by using drama text significantly stimulate where it gained a development, the mean score of pretest is 6,63, which is categorized as fairly good and posttest is 7.83 its categorized as good (8.05 > 6.80) and the standard deviation was 0.47 pretest and standard deviation of posttest was 0.62. The T score is ( -18.90) the probability test is (1,666) so the result of score -18.90 < 1,666. H0 is reject. It means that there is significantly between pretest and posttest by rereading and discussing drama text to stimulate English performance. The questionnaires were used to find out the students interest after being taught through rereading and discussing the local drama text. Based on the result of data analysis, the researcher concluded that rereading and discussing drama text from local history can stimulate the students’ English performance in two aspects they are English performance that consists of speaking accuracy, fluency, and comprehensibility, Furthermore, rereading and discussing activities generate aspects imitative, intensive, responsive, transactional (dialogue), interpersonal, and extensive.